PERANCANGAN SISTEM INFORMASI AKUNTANSI PENJUALAN BERBASIC WEB MENGGUNAKAN METODE RAD DI PT CORBEC COMMUNICATION BANDUNG - Lensa Ananda Riadini; Falaah Abdussalaam; Karyadi, Karyadi (Media Bina Ilmiah, 2024)
The purpose of this research is to develop a sales accounting information system at PT Corbec Communication Bandung. After the research was carried out, there were problem factors, namely the data management process which was still simple so that it was possible for errors to occur in recording sales data and errors in the process of calculating sales transactions so that they had to double-check this which made the process of information about sales reports slow. These problems can be overcome by creating a sales accounting information system that will simplify the process of managing sales data so that the information needed will be easily and quickly obtained. This accounting information system is designed using the PHP programming language with MySQL as its database and the development method used is the RAD method. Testing this sales application using blackbox testing. Based on the design results and the results of testing the sales application of PT Corbec Communication Bandung, it can be concluded that the Rapid Application Development method greatly assists the processing of making sales applications more accurate and faster